SENSITIVITY ANALYSIS OF HYDRAULIC FRACTURING SCENARIO IN SHALE GAS SIMULATION MODEL : FRACTURE SPACING AND FRACTURE HALF LENGTH. - Rayner
Unconventional gas reservoir developments in North America are improving nowadays. Shale gas is one majority type of unconventional hydrocarbons which has been developed there. Shale has unique characteristics which cause necessarity of different treatments compared with conventional hydrocarbons. The characteristics include very low permeability, many fractures with micro size, and sensitivity of contact fluids. Hydraulic fracturing is a stimulation process which needed to improve gas well productivity in shale gas fields. Because of that, it's really important to gather more information about this hydraulic fracturing process. In a shale gas hydraulic fracturing process, there are many parameters which have important roles and affect each other. In this study, there's an analytical process to observe the effect of two of those parameters. The purpose of this study is to explain the effect of half-fracture length of hydraulic fracturing and hydraulic fracture spacing to production and reservoir aspects in a shale gas field and to find connection between those two parameters in the determination of IGIP. Beside that, this study explains the process in determining equations to find recovery factor, plateu time, and Initial Gas In Place of modeled shale gas reservoir. There are combination scenarios of those two parameters in this study mentioned one the above. The information data in this study is gathered from publication about a shale gas field in USA. This study uses petroleum softwares to calculate reservoir data and make computerial model of shale gas field.